The ethnobotanical study of edible and medicinal plants in the home garden of Batak Karo sub-ethnic in North Sumatra, Indonesia - MARINA SILALAHI; NISYAWATI NISYAWATI (Biodiversitas Journal of Biological Diversity, 2018)
Silalahi M, Nisyawati. 2018. The ethnobotanical study of edible and medicinal plants in the home garden of Batak Karo sub-ethnic in North Sumatra, Indonesia. Biodiversitas 19: 229-238. The cultivation of plants in home gardens for self-sufficiency is a long tradition in Karo District, but the documentation of local knowledge about edible and medicinal plants in home gardens in Karo District is limited. This study aimed to (i) document the uses of the edible and medicinal plants in home gardens; (ii) to analyze the diversity of edible and medicinal plants in home gardens. Data were collected using the ethnobotanical surveys and interviews methods. The Shannon Weiner and Margalef indices were calculated to determine the diversity levels of medicinal and edible species in the home gardens of Karo ethnic. The surveys were conducted in 30 home gardens (7 villages), Karo District, North Sumatra. The 85 recorded species belonged to 43 families, and 73 genera were used as edible and medicinal plants. The plants studied in the home gardens used for human consumption were i.e. fruits, vegetables, spices, tubers and medicinal plants. Among 85 plant species growing in home gardens, 52 species were cultivated, and the rest were semi cultivated. Home gardens had the Shannon Wiener index ranging from 1.164 to 3.123 while Margalef index ranging from 0.929-2.531.